A pre-processing method for digital image correlation on rotating structures. (1st May 2021) - Huang, Jiasheng; Zhou, Kuanyong; Chen, Wei; Song, Hanwen
Highlights: A method is introduced to improve the performance of DIC on rotating structures. A method is introduced to detect the structural phase in an image. Both methods are proved to be effective and efficient through tests. Centrifugal hardening effect of rotation is observed in operational conditions. Abstract: Inter-frame structural motions are required to be small for classic Digital Image Correlation (DIC) algorithms, which severely limits the application of the technique in large rotation cases. To solve the problem, multiple methods to obtain initial guesses of deformation parameters have been introduced over recent years. However, the success rate is still limited by rotation angles and the efficiency is low due to extra calculations with these methods. To further develop the application of DIC in large rotation cases, Phase Mapping Method (PMM) is introduced in this paper. The principle of the proposed method is to rearrange the obtained images to be sorted by the structural rotating phases, which are previously mapped into the range of 0 to 2 π . As a result, for an image set of n frames, the average inter-frame rotating angle is reduced to 2 π n - 1, and the original image set is transferred into an equivalent semi-static one by PMM. Additionally, a fast phase-detection approach is introduced to automate PMM in cases that the structural rotating speeds are unknown. By performing multiple tests, it is proved that PMM, as a pre-processing method, can significantly improve the success rate and the efficiency of DIC, whether used alone or concurrently with other algorithms. The first natural frequencies and mode shapes of a rotating beam under different rotating speeds are extracted through vibration test, from which the hardening effect is observed.